Изменение состава зоопланктона по мере «старения» вод апвеллинга у юго-западной Африки - Билева, О.К. (Вестник зоологии, 1977)
According to the data of the 27th cruise of the research ship "Mikhail Lomonosov", a high degree of complicacy of the zoocenosis in the upwelling zone is found out. Zoocenosis consists of neritic, farneritic and ocean organisms of epiplanktonic and interzonal complexes. There are mass species. In the zone of water dipping the ocean species are highly predominant. The total amount of species is 2.5 times as high as in the upwelling zone. No mass organisms are observed.